Synthesis of DNA and RNA Oligonucleotides Containing a Dual-Purpose Selenium-Modified Fluorescent Nucleoside Probe - Nuthanakanti, Ashok (Curr Protoc Nucleic Acid Chem, 2020)
Development of efficient tools that would enable direct correlation of nucleic acid structure and recognition in solution and in solid state at atomic resolution is highly desired. In this context, we recently developed dual-purpose nucleoside probes made of a 5-selenophene-modified uracil core, which serves both as a conformation-sensitive fluorophore and as an X-ray crystallography phasing agent. In this article, we provide a detailed synthetic procedure to synthesize the phosphoramidites of 5-selenophene-modified 2’-deoxyuridine and 5-selenophene-modified uridine analogs. We also describe their site-specific incorporation into therapeutically relevant DNA and RNA oligonucleotide motifs by an automated solid support synthesis protocol. The dual-purpose and minimally invasive nature of the probes enables efficient analysis of the conformation and ligand binding abilities of bacterial decoding site RNA (A-site) and G-quadruplex structures of the human telomeric overhang in real time by fluorescence and in 3D by X-ray crystallography.